Relationship between Physical Activity and Coping Styles in the Face of Covid-19 Epidemic among Women in Ahvaz - Masoumeh Hosseinzadeh; Maryam Janbozorgi (Fasa University of Medical Sciences, 2022)
Background & Objective: Decreased levels of physical activity during the COVID-19 epidemic can cause physical and psychological problems for the individual. Therefore, the aim of this study was to evaluate the relationship between physical activity and control coping styles in the face of the Covid-19 epidemic in Ahvaz, Iran. Materials & Methods: This study is a descriptive-analytical cross-sectional study and the research population includes females in Hamidiyeh Ahvaz, Iran, who were studying in 2019-2020. In this regard, 208 females were selected based on Cochran's formula and random sampling for participation in the study. Beck's physical activity questionnaires and Coping Styles Questionnaire in the face of the COVID-19 epidemic were used to collect data. Pearson correlation coefficient was used to establish statistical relationships. Results: The results only showed a significant relationship between social support coping style and physical activity (physical activity related to leisure time) (r= 0.142, p= 0.044). There was no significant relationship between physical activity (related to work, sport, leisure time and total) and any of the other coping styles (Confrontation, Avoidance, Self-control, Responsibility, Escape and avoid, Problem solving, Positive estimation) (p≥0.05). Conclusion: During the COVID-19 epidemic, physical activity related to leisure time was positively associated with social support coping style but all other cases we did not observe a significant relationship between physical activity and coping styles with Covid-19.